Alkaloid profiling and anticholinesterase activity of south american Lycopodiaceae species - Konrath, Eduardo Luis (2011)
The alkaloid extracts of four Huperzia and one Lycopodiella species, from Brazilian habitats, were tested for their in vitro anticholinesterase activities. IC(50) values showed a potent acetylcholinesterase inhibition for H. reflexa (0.11 ± 0.05 μg/mL), followed by H. quadrifariata (2.0 ± 0.3 μg/mL), H. acerosa (5.5 ± 0.9 μg/mL), H. heterocarpon (25.6 ± 2.7 μg/mL) and L. cernua (42.6 ± 1.5 μg/mL). A lower inhibition of butyrylcholinesterase was observed for all species with the exception of H. heterocarpon (8.3 ± 0.9 μg/mL), whose alkaloid extract presented a selectivity for pseudocholinesterase. Moreover, the chemical study of the bioactive extracts performed by GC-MS, revealed the presence of a number of Lycopodium alkaloids belonging to the lycopodane, flabellidane and cernuane groups. Surprisingly, the potent acetylcholinesterase inhibitors huperzines A and B were not detected in the extracts, suggesting that other alkaloids may be responsible for such an effect.